Internal Transfers – Internal Medicine Department evaluation in a Central Hospital - Carrola, Paulo; Parente, Francisco; Duarte, Manuela; Devesa, Nuno; Dias, Patrícia; Alexandrino, M. B.; Moura, J. J. (Portuguese Journal Internal Medicine, 2004)
Introduction and Objectives – Coimbra´s University Hospital has a significant rate of Internal Transfers (IT). The authors analysed this parameter in the Internal Medicine department - Service II with the objective of evaluating the departments’ interface, namely resource utilisation and cooperation with other departments of the same Hospital. Material and methods – Amongst the admissions to the Internal Medicine department - Service II, the ones with a discharge date between the January 1st 2000 and December 31st 2001 were selected. General indicators and indication for transfer were studied, particularly the subgroups involving transfers to the Intensive Care Unit (ICU) and Surgical procedures (Cir). The economic impact was quantified using relative weight methodology and financial determinations were based on the Diagnosis Related Groups (DRG). Results – The number of IT episodes was 154 (6.3 % of the admissions to the Internal Medicine department - Service II). The mortality rate was 16.2 % and the average length of admission was 27.7 days (higher than the Internal Medicine department – Service II general average – 8.9 % and 8.7 days). The most significant IT target department from the Internal Medicine department – Service II was General Surgery (34 %). On the other hand, the ICU showed the highest rate of IT (4.8 %) to the Internal Medicine department – Service II. The subgroups involving Surgery (n=53; 34.4 %) and ICU (n=43; 27.9 %) showed a different profile from the overall number of transfers, namely the admission days attributed to the Internal Medicine department – Service II of the ICU patients (n=431) and urgent surgery (n=24). The impact on the DRG financial reimbursement in the IT group was significant. Conclusions – The authors outline some aspects of the analysis: 1. The IT corresponded to a more differentiated care group; 2. The importance of the post-ICU care group in the overall results signalled the need for human and material resources adequate for proper care of these patients; 3. The existence of non-programmed surgery as a point of interest, namely the need for accurate identification in the emergency room of the cases with surgical indication; 4. The importance of the IT parameter in the model for financial evaluation of the Integrated Responsibility Centres (IRC).